Laparoscopic management of gastric volvulus, diaphragmatic eventration and wandering spleen in a child. Issue 6 (23rd June 2021) - Kataria, Riya; Sundaram, Jegadeesh; Agarwal, Prakash; Lal, Tusharindra
Abstract : Gastric volvulus (GV) and wandering spleen (WS) associated with eventration of diaphragm share a common pathological cause of absence or laxity of intraperitoneal ligaments. We herein report a rare case of a 13-year-old child presenting with an acute GV, WS, diaphragmatic eventration and an ectopic ascended kidney managed with a laparoscopic approach.